Development and evaluation of an Individualized Outcome Measure (IOM) for randomized controlled trials in mental health. Issue 4 (17th July 2015) - Pesola, Francesca; Williams, Julie; Bird, Victoria; Freidl, Marion; Le Boutillier, Clair; Leamy, Mary; Macpherson, Rob; Slade, Mike
Abstract: Pre‐defined, researcher‐selected outcomes are routinely used as the clinical end‐point in randomized controlled trials (RCTs); however, individualized approaches may be an effective way to assess outcome in mental health research. The present study describes the development and evaluation of the Individualized Outcome Measure (IOM), which is a patient‐specific outcome measure to be used for RCTs of complex interventions. IOM was developed using a narrative review, expert consultation and piloting with mental health service users ( n = 20). The final version of IOM comprises two components: Goal Attainment (GA) and Personalized Primary Outcome (PPO). For GA, patients identify one relevant goal at baseline and rate its attainment at follow‐up. For PPO, patients choose an outcome domain related to their goal from a pre‐defined list at baseline, and complete a standardized questionnaire assessing the chosen outcome domain at baseline and follow‐up. A feasibility study indicated that IOM had adequate completion (89%) and acceptability (96%) rates in a clinical sample ( n = 84). IOM was then evaluated in a RCT (ISRCTN02507940). GA and PPO components were associated with each other and with the trial primary outcome. The use of the PPO component of IOM as the primary outcome could be considered in future RCTs. Copyright © 2015 John Wiley & Sons, Ltd.